ANALISIS PERBAIKAN SUDUT PUNTIR DENGAN METODE ITERASI BILANGAN REYNOLDS PADA TURBIN ANGIN SUMBU HORIZONTAL SKALA MIKRO - Samira Al Zaitun (2022)
Small-scale horizontal axis wind turbines are a solution to the conversion of electrical energy. The development of turbines, especially small scale, has developed rapidly, and the design of wind turbine blades is an aspect that needs to be considered in optimizing the performance of wind turbines extracting wind energy into motion. Designing the geometry of a wind turbine without pitch control requires the design of blades that take into account the value of the angle of attack from the relative wind speed. In another study, wind speed calculations used free wind speed, but in this study, improvements were made to the blade design by calculating wind speed using the sum of wind speed vectors before passing the blades with tangential speed after passing through the blades to minimize the occurrence of stalls (conditions of decreasing the value of the lifting coefficient as a result of the angle of attack crossing the critical limit) and making the power performance of the coefficient increase. The research method uses two simulation methods, namely the Blade Element Momentum Method and Computational Fluid Dynamics. In the Computational Fluid Dynamics simulation method using Fluent with meshing, the result of the power coefficient value on the wind turbine blades for design repair is 0.345 and before the repair is 0.340, the results obtained are that the turbine performance value after repair increases compared to before repair.